Effect of home-based training focused on increasing maximum step length in walking function of children with cerebral palsy. (2nd November 2019) - Kimoto, Minoru; Yonetsu, Ryo; Okada, Kyoji; Horioka, Wataru; Kondou, Takanori; Sasaki, Makoto; Sakamoto, Hitoshi
Abstract: Background: Developing a home-based training (HBT) program can increase gait performance in children with cerebral palsy (CP) who receive insufficient clinical or institutional-based therapy. Objective: To investigate the effect of HBT program focusing on increasing maximum step length (MSL) in walking function of children with spastic diplegic CP. Methods: Although this was a randomized controlled trial, the subjects had known own allocation. To determine the change as the effect, MSL variables and step length at the end of the HBT program (second assessment, 8 weeks) and 8 weeks after the HBT program (third assessment, 16 weeks) were subtracted from those at baseline (0 week). Results: MSL ( p  = .005) and step length during the walk assessment ( p  = .021) significantly increased in the experimental group compared with those in the control group. For step length, the effect size was 1.06 (95% confidence interval [0.14, 1.97]). The scores (0 to 16 weeks) of MSL ( p  = .019) and step length ( p  = .018) in the experimental group significantly changed compared with those in the control group. Conclusion: MSL and step length improved after training and persisted 8 weeks after the HBT program. These findings can be useful for effective training practices in a home environment.